2005
DOI: 10.1007/s10555-005-5045-3
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in head and neck cancer: Molecular biology and clinicopathological correlations

Abstract: Human papillomaviruses are known to cause cancers of the cervix and other anogenital tract sites. Epidemiologic and molecular pathology studies have also suggested that HPV infection may be associated with cancers of the head and neck. Modes of transmission of HPV infection in the head and neck region have not been fully resolved; however, perinatal transmission and an association between sexual behavior and risk for HPV-positive cancers have been presented. Among the HPV types infecting the mucosa, high-risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 92 publications
1
24
0
6
Order By: Relevance
“…4,5,17,22,27 Szentirmay et al concluded that epidemiologic and extensive laboratory evidence supports the association between HPV and a subset of cancers of the oral cavity, orapharynx, and larynx. 28 In addition, they pointed out that HPV-positive cancers of the head and neck region were more likely to have verrucous histological features. 28 Our findings are in agreement with previous reports of the presence of HPV DNA in VC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,17,22,27 Szentirmay et al concluded that epidemiologic and extensive laboratory evidence supports the association between HPV and a subset of cancers of the oral cavity, orapharynx, and larynx. 28 In addition, they pointed out that HPV-positive cancers of the head and neck region were more likely to have verrucous histological features. 28 Our findings are in agreement with previous reports of the presence of HPV DNA in VC.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, they pointed out that HPV-positive cancers of the head and neck region were more likely to have verrucous histological features. 28 Our findings are in agreement with previous reports of the presence of HPV DNA in VC. 4,17,22,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Ebben a régióban HPV-fertőzés és ezzel párhuzamosan laphámrákok előfordulási gyakoriságának emelkedése nők-nél figyelhető meg, amely a szexuális szokások megválto-zásával függhet össze [14][15][16]. Összesen 136 fej-nyaki laphámrákot felölelő korábbi munkánkban az oropharingealis rákok 48,5%-a, a gégerákok 35,7%-a volt HPVpozitív, és Magyarországon is az alkoholt nem fogyasztó HPV-betegek körében a nők voltak túlsúlyban [3]. Ezek a korábbi adatok nagyon jól korrelálnak azzal a jelenlegi megfigyelésünkkel, hogy a 2009 és 2015 közötti időin-tervallumban férfiaknál egyik fej-nyaki lokalizációban sem változott a megbetegedések és halálozások aránya,…”
Section: Következtetésekunclassified
“…A rendelkezésre álló adatok viszont arra utalnak, hogy döntően a magas carcinogen rizikójú (HR) HPV-típus lehet felelős a méhnyakrák és rákmeg-előző állapotok kialakulásáért. Az L1 gén DNS-szekvenciája alapján a genetikailag rokon HPV-típusok elkülö-nülő alcsoportokat alkotnak [2,3]. Legutóbb az IACR Working Group foglalkozott a HPV-rizikócsoportokkal és a genetikai hasonlóság, valamint a méhnyakrákban előforduló gyakoriság alapján új HPV-csoportosítást javasolt [4].…”
unclassified
“…[78] The organisation of the life cycle of HPVs in the development of lower genital tract neoplasias is well established. [79][80][81][82] Retrospective studies have reported that almost all the women with cervical cancers are infected with HPV and in the more severe cases, that are squamous cell carcinomas, HPV16 is the most prevalent type observed in 90% of the cases [40,52,83,84] Ten percent of the cervical cancers are adenocarcinomas that are mostly caused by HPV infections. [40] Women with HPV16 (61%) and HPV18 (10%) were shown to have 200 fold higher risks for the development of cervical cancers.…”
Section: Lower Genital Tract Neoplasias: Cervical Vaginal and Vulvarmentioning
confidence: 99%